Dual immunotherapy alternating with anti-PD-1 antibody plus liposomal doxorubicin show good efficacy in prostate epithelioid hemangioendothelioma: a case report - Zhang, Jie; Ye, Qin; Yang, Xudan; Li, Tenglong; Huang, Shan; Zhou, Ping; Feng, Yumei; Liu, Hao; Xie, Ke (Frontiers in Immunology, 2024)
Epithelioid hemangioendothelioma is a rare vascular malignancy, and currently, there is no standard treatment regimen for this disease and existing treatment options have limited efficacy. In this case report, we present a patient with lung and lymph node metastases from prostate epithelioid hemangioendothelioma who achieved a significant partial response. This was accomplished through alternating nivolumab therapy with ipilimumab and liposomal doxorubicin, resulting in a progression-free-survival more than 6 months to date. The treatment was well-tolerated throughout. Our report suggests that dual immunotherapy alternating with anti-PD-1antibody plus doxorubicin may be a potential treatment modality for epithelioid hemangioendothelioma. However, larger sample studies are necessary to ascertain the effectiveness of this treatment strategy and it is essential to continue monitoring this patient to sustain progression-free survival and overall survival.